Application Of Nearest Neighbor Analysis Methods For The Distribution Of Small Storks (Egretta Garzetta) In The Mangrove Area North Sumatra - Trima Lestari; Fibri Rakhmawati; Ismail Husein (RANGE: Jurnal Pendidikan Matematika, 2024)
The penetrating waterbird on the east coast of North Sumatra is Egretta Garzetta. It is a kind of water bird that lives in water or parts of wetlands. The presence of waterbirds is an important indicator to evaluate the environmental quality and productivity of wetlands. Bird distribution patterns are needed to overcome problems related to habitat, such as food availability and population size. This study aims to apply themethod Nearest Neigbord Analysis to the distribution pattern of Egretta Garzetta in the Mangrove area of North Sumatra. This study uses a quantitative approach to the type of applied research (Applied Research). The type of data used in this research is secondary data. Analysis of the data in this study using Nearest Neighbor Analysis. The pattern of the spread of Egretta Garzetta in the Mangrove areas in North Sumatra have clumped pattern (clustered).The results from Nearest Neighbor Analysis show that the index value of the clustered distribution pattern can be caused by the abundance of food sources in a habitat.